2019
DOI: 10.1177/1362361319855851
|View full text |Cite
|
Sign up to set email alerts
|

Parent–Child Interaction Therapy for children with autism spectrum disorder and a matched case-control sample

Abstract: Parent–Child Interaction Therapy is an empirically based, behavioral parent training program for young children exhibiting disruptive behaviors. Parent–Child Interaction Therapy shows promise for treating disruptive behaviors in children with autism spectrum disorder. Treatment processes (i.e. treatment length and homework compliance), parenting skills, parenting stress, and behavioral outcomes (i.e. disruptive and externalizing behaviors and executive functioning) were compared in 16 children with autism spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 75 publications
2
11
0
4
Order By: Relevance
“…Por lo que respecta a la metodología de las intervenciones, algo más de la mitad de los estudios, un 52'17%, ha optado por el ensayo controlado aleatorizado (Borgi et al, 2015;Chan et al, 2012;Chan et al, 2014;de Vries et al, 2015;Escolano et al, 2019;Kenworthy et al, 2014;Morgan et al, 2018;Naeeimi et al, 2013;Pan et al, 2017;Parladé et al, 2020;Phung y Goldberg, 2019;Tachibana et al, 2013;Tse et al, 2019). Esto denota un alto grado de fiabilidad sobre las evidencias científicas extraídas en cada uno de ellos.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Por lo que respecta a la metodología de las intervenciones, algo más de la mitad de los estudios, un 52'17%, ha optado por el ensayo controlado aleatorizado (Borgi et al, 2015;Chan et al, 2012;Chan et al, 2014;de Vries et al, 2015;Escolano et al, 2019;Kenworthy et al, 2014;Morgan et al, 2018;Naeeimi et al, 2013;Pan et al, 2017;Parladé et al, 2020;Phung y Goldberg, 2019;Tachibana et al, 2013;Tse et al, 2019). Esto denota un alto grado de fiabilidad sobre las evidencias científicas extraídas en cada uno de ellos.…”
Section: Discussionunclassified
“…Por lo tanto, los cuatro grandes grupos en los que se pueden dividir para clasificarlos son: aquellas que hacían uso de las TIC, las que se desarrollaban en un aula o en casa mediante actividades relativa o completamente estáticas, aquellas que requerían cierta actividad física o movimiento y las que no se pueden clasificar en ninguno de los anteriores. Los dos más utilizados fueron las actividades en el aula y en casa con materiales simples como, por ejemplo, fichas que se dio en un 43'48% de los casos (Acero et al, 2017;Baltruschat et al, 2011;Baltruschat et al, 2012;Bravo y Frontera, 2016;Escolano et al, 2019;Hajril et al 2017;Kenworthy et al, 2014;Morgan et al, 2018;Parladé et al, 2020;Tachibana et al, 2013) y las actividades que requerían cierta actividad física, que se corresponde con el 26'09% de los casos (Borgi et al, 2015;Hilton et al, 2014;Nakutin y Gutierrez, 2019;Pan et al, 2017;Phung y Goldberg, 2019;Tse et al, 2019).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Finally, Parladé et al [114], performed a study to examine the influence of a PCIT-based intervention in children with behavioral problems and autism spectrum disorders. The goal was to observe changes that may occur in parental skills, parental stress, and child behaviors.…”
Section: Parent-child Interaction Therapy (Pcit)mentioning
confidence: 99%
“…However, several studies have demonstrated that the father's involvement enhances treatment outcome, so all family members/caregivers are encouraged to participate in PCIT (Bagner, 2013). Interestingly, in most PCIT case studies from the United States, fathers were actively involved in treatment both inside and outside of the session room (e.g., Armstrong et al, 2014Armstrong et al, , 2015Cooper-Vince et al, 2016;Gordon & Cooper, 2016;Parlade et al, 2020).…”
Section: Treatment Implications Of the Casementioning
confidence: 99%